2007
DOI: 10.1111/j.1469-1809.2007.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphic Sites in the OCA2 Gene with Eye Colour Using the Tree Scanning Method

Abstract: SummaryA number of genes are considered to affect normal variation in human pigmentation. Recent studies have indicated that OCA2 is the crucial gene involved in the high variation of iris colour present among populations of European descent. In this study, eleven polymorphisms of the OCA2 gene were examined in search of their association with different pigment traits. The evolutionary tree scanning method indicated that the strongest phenotypic eye colour variation is associated with the branch defined by non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…The OCA2 gene encodes a protein that is an integral part of the melanosomal membrane and is responsible for regulation of pH inside the melanosome, [55][56][57] which, in consequence, has an influence on the activity of the enzyme tyrosinase, which has a crucial role in the synthesis of the pigment melanin. The important role of OCA2 in eye colour determination was confirmed in many studies, 11,13,28,31,[58][59][60][61] and further investigations revealed that regulation of OCA2 expression through the neighbouring HERC2 gene might have a crucial role. 16,20 A functional effect was assigned to the rs12913832 position located in a conservative segment of the intron 86 of the HERC2 gene, which contains transcription factor-binding sites.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The OCA2 gene encodes a protein that is an integral part of the melanosomal membrane and is responsible for regulation of pH inside the melanosome, [55][56][57] which, in consequence, has an influence on the activity of the enzyme tyrosinase, which has a crucial role in the synthesis of the pigment melanin. The important role of OCA2 in eye colour determination was confirmed in many studies, 11,13,28,31,[58][59][60][61] and further investigations revealed that regulation of OCA2 expression through the neighbouring HERC2 gene might have a crucial role. 16,20 A functional effect was assigned to the rs12913832 position located in a conservative segment of the intron 86 of the HERC2 gene, which contains transcription factor-binding sites.…”
Section: Discussionmentioning
confidence: 79%
“…Further studies confirmed the highest significance of rs12913832 in eye colour determination and also showed that in spite of strong linkage between HERC2 and OCA2, one position in the OCA2 gene; that is, rs1800407, remains independently associated with eye colour and has a modulatory role for rs12913832 in HERC2. 16,31 Our analyses showed that these two SNP positions were in strong LD and all the reconstructed haplotypes were found to be significantly associated with eye colour (Table 1). Moreover, both the SNPs were selected by ReliefF filtering in case of three from four eye colour models ( Table 1).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Many of their variants may cause serious pigmentation disorders, but at the same time other polymorphisms may be involved in physiological pigmentation variation. MC1R has been the subject of the most thorough studies, but initial results have also been replicated in various populations for such genes as ASIP, OCA2, and SLC45A2 (Rees 2004;Kanetsky et al 2002;Rebbeck et al 2002;Frudakis et al 2003;Bonilla et al 2005;Duffy et al 2007;Branicki et al 2008;Graf et al 2005;Fernandez et al 2008). The MC1R gene is one of the major pigmentation genes.…”
Section: Introductionmentioning
confidence: 99%